Computer Games Development Class with Appreciative Learning Approach: From the Perspective of Bloom's Taxomony. - Ali, Wan Zah Wan; Eow Yee Leng; Mahmud, Rosnaini; Baki, Roselan (Pertanika Journal of Social Sciences & Humanities, 2012)
Both computer games development and appreciative learning approach are still at the infancy stage of utilization at educational setting. The purpose of this study was to explore what lower secondary students learned from the application of appreciative learning approach in computer games development class. Triangulated data comprising of interviews, logbooks, visual, captures, researchers' observations, and games were produced. NVivo software was used to support data management. The compiled codes were clustered to create themes pertinent to Bloom's taxonomy. As a result, computer games development within appreciative learning approach environment was found as positively related to students' cognitive, affective, and psychomotor development. Nevertheless, caution is warranted in making inferences as different students gained different learning experiences and outcomes, analogous to different players generated different outcomes in computer games.